2019
DOI: 10.1002/anie.201901035
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Monitoring of Propagative Fluctuation of Ascorbate in the Live Rat Brain during Spreading Depolarization

Abstract: Spreading depolarization (SD) occurs frequently in the injured brain, and its neurochemical effects are detrimental to brain function. We report the first observation that the release of ascorbate,animportant neurochemical in the brain, is closely accompanied with SD.Ascorbate was monitored with carbon nanotube (CNT)-sheathed carbon fiber microelectrodes (CFEs). This system features high selectivity and temporal/ spatial resolution. With our sensor,w eo bserved as ignificant increase in the concentration of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 55 publications
2
55
0
Order By: Relevance
“…The resolved typical voltammograms (Figure 3 b) showed that during the spreading depression process, the concentrations of AA and DA first rapidly increase (by 114 μmol L −1 and 2 μmol L −1 for AA and DA, respectively), then drop to their basal level gradually, whereas the ion concentration decreases (by 130 mmol L −1 ) first, then recovers to its basal level. The variations of extracellular ions and neurotransmitters are consistent with previously reported reaction‐diffusion mechanism of spreading depression propagation, [21, 24] although the mechanism of AA release is still elusive [22a, 25] . In this regard, the DLV platform offers a powerful tool to comprehensively delineate multiple neurochemical fluctuations in the living rat brain during spreading depression process.…”
Section: Resultssupporting
confidence: 84%
“…The resolved typical voltammograms (Figure 3 b) showed that during the spreading depression process, the concentrations of AA and DA first rapidly increase (by 114 μmol L −1 and 2 μmol L −1 for AA and DA, respectively), then drop to their basal level gradually, whereas the ion concentration decreases (by 130 mmol L −1 ) first, then recovers to its basal level. The variations of extracellular ions and neurotransmitters are consistent with previously reported reaction‐diffusion mechanism of spreading depression propagation, [21, 24] although the mechanism of AA release is still elusive [22a, 25] . In this regard, the DLV platform offers a powerful tool to comprehensively delineate multiple neurochemical fluctuations in the living rat brain during spreading depression process.…”
Section: Resultssupporting
confidence: 84%
“…Lightweight and mechanically strong protein‐based fibers have attracted increasing attention over the past decades due to the combination of high strength and high toughness. In comparison with traditional synthetic fibers, such as nylon and Kevlar fibers, protein fibers exhibit enhanced biocompatibility, biodegradability, and sustainability, offering great opportunities for biomedical applications . To date, the outstanding mechanical properties of natural spider silks have inspired scientists to construct biomimetic protein fibers from the recombination of spider silk proteins .…”
Section: Figurementioning
confidence: 99%
“…To further simplify the preparation of CNT‐based electrodes, we recently fabricated single‐walled carbon nanotubes modified electrodes (SWNT‐CFEs) by the electrophoretic deposition (EPD) of SWNTs onto the surface, [15] a process that is highly controllable and reproducible. The as‐prepared electrodes showed fast electron‐transfer kinetics and greatly improved performance in electrochemical oxidation of AA.…”
Section: Selective Detection By Using Electrocatalysts To Modulate the Interfacial Electron Transfermentioning
confidence: 99%